5h+2(11-h)-5=

Simple and best practice solution for 5h+2(11-h)-5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5h+2(11-h)-5= equation:


Simplifying
5h + 2(11 + -1h) + -5 = 0
5h + (11 * 2 + -1h * 2) + -5 = 0
5h + (22 + -2h) + -5 = 0

Reorder the terms:
22 + -5 + 5h + -2h = 0

Combine like terms: 22 + -5 = 17
17 + 5h + -2h = 0

Combine like terms: 5h + -2h = 3h
17 + 3h = 0

Solving
17 + 3h = 0

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-17' to each side of the equation.
17 + -17 + 3h = 0 + -17

Combine like terms: 17 + -17 = 0
0 + 3h = 0 + -17
3h = 0 + -17

Combine like terms: 0 + -17 = -17
3h = -17

Divide each side by '3'.
h = -5.666666667

Simplifying
h = -5.666666667

See similar equations:

| 4(4y-1)+3-2(3+y)=0 | | -3(4-6y)+7(-y+5)=-8 | | (a+6)(a*2-8a+8)= | | 6c^2+7cd-5d^2= | | 2(x+3)-3x=5-x+1 | | 2x+5+6x-20=180 | | 8x-2(x+5)=5(2x-6) | | 9x-3y=27 | | 6a-47-2a=8a-15 | | 6x-5=-2x+11 | | 3(x+4)-2(x-1)=4(x+4) | | 75-3n+6n=12+15n-2+3n+20 | | -5+3m=3-m | | -3(-2)+6+-2= | | -1+3(x-1)=8x-5(x-2)-14 | | 7x-40-27x=10x+6+36 | | x^2+18x+53=594 | | x^2-5x-11x=0 | | 9x-7=4x+1 | | 9d-4=49 | | 30x=-480 | | x+x*.05=1065.64 | | x+x*.05=1000 | | 3x-17=-14 | | x-16=-30 | | 25w^2-10w+1=0 | | 7-p=3+3p | | 8t-6(-2+7t)=9+t-11 | | X+(X*0.05)=1000 | | 4(5)x-2(3)y=13 | | x^2-2x-6= | | 3y+2y-5=15+y |

Equations solver categories